Eksplorasi Tana Toraja Dalam Media Game Digital Genre Puzzle - Diajeng Fitri Aulia Niza; Samuel Gandang Gunanto; Andri Nur Patrio (Journal of Animation and Games Studies, 2019)
Lost in Toraja game is an educational game with adventure-puzzle genre. The main character is Orion, who explores Tana  Toraja,  South Celebes, one of local area  in Indonesia. Orion is a character from West Java, and his intention to Tana Toraja is looking for her missing sister when she’s on her trip there.Lost in Toraja has a playtime around 30-45 minutes. The player will become a main character, who enter the game area, and they have to find the way out. Each area has several puzzle that player has to solved. The game was made using digital technique in Unity game engine, and will be build in Android platform and Windows platform.The game’s intention is to spread Tana Toraja culture among Indonesian’s citizen itself, even into foreign country. Game is a pleasing media to have fun and leart at once.Keywords: Game, Adventure-Puzzle, 2D, Education, Tana Toraja